Respostas

2014-02-06T02:37:29-02:00
OI SARA

a)5(3-x)+2(X+1)=-X+5
 15-5x+2x+2+x=5
   -5x+2x+x=5-15-2
     -2x=-12
      x=6
S=(6)

b)5x+20(1-x)=5
  5x+20-20x=5 divide tudo por5
    1x+4-4x=1
        -3x=1-4
          -3x=-3
 x=-3/-3
 x=1
   S=(1)    
  
c)5b²-20=0
    5B²=20 DIVIDE TUDO POR 5
       b²=4
       b1=2
       b2=-2
S=(2,-2)

d)5m²-3m=0
 A=5,B=-3 , C=0
Δ=b²-4.A.C
Δ=-3²-4.5.0
Δ=9
M1=+3+3/2.5 =6/10=3/5
M2=+3-3/10
 M2=0
S=(0,3/5)

e)t²-8t=0
A=1,B=-8 ,C=0
   
Δ=B²-2.A.C
 A=1,B=-2 C=0
Δ=64
t=-B+-√Δ/2.A
t1= 8+8/2=0
t1=16/8
  t1=2

t2=8-8/2
t2=0
  
S=(0,2)

1 5 1